2018
DOI: 10.18433/jpps30212
|View full text |Cite
|
Sign up to set email alerts
|

Progress on Active Analgesic Components and Mechanisms of Commonly Used Traditional Chinese Medicines: A Comprehensive Review

Abstract: Many clinical diseases are accompanied by the symptoms of pain, and the degree of pain is closely related to the patients’ suffering. Therefore, effectively relieving pain has become one of the vital concerns of clinical treatment and analgesic drug research. Non-opioid drugs are mainly used for the clinical treatment of mild to moderate pain, whereas opioid drugs are mainly used for treating moderate to severe pain. However, opioid drugs easily elicit adverse reactions, such as gastrointestinal discomfort, ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 164 publications
0
20
0
Order By: Relevance
“…These cytokines are also responsible for excessive sensory innervation and the development of chronic pelvic pain (Kobayashi et al, 2014;. The results showed that Chinese herbs could reduce pain associated with the regulation of neurotransmitters (5-hydroxytryptamine, dopamine, and nervous system associated pathways (Wang et al, 2018).…”
Section: The Pain Relief Functionmentioning
confidence: 99%
“…These cytokines are also responsible for excessive sensory innervation and the development of chronic pelvic pain (Kobayashi et al, 2014;. The results showed that Chinese herbs could reduce pain associated with the regulation of neurotransmitters (5-hydroxytryptamine, dopamine, and nervous system associated pathways (Wang et al, 2018).…”
Section: The Pain Relief Functionmentioning
confidence: 99%
“…Interestingly, there is a significant move towards the testing of natural products during this period, particularly with respect to anti-oxidant compounds. This might be part of the global interest in dissecting the mechanisms and active ingredients found in herbal and traditional medicines (Li & Weng 2017;Wang et al 2018), but also likely reflects a desire to develop agents that have minimal toxicities that would otherwise limit future development, as occurred in the amifostine story.…”
Section: Current State Of Play (2013-2018)mentioning
confidence: 99%
“…2,4 Non-opioid drugs have been used in treatment of mild to moderate pain, while opioid drugs are used in the treatment of moderate pain. 5 Conventional therapy for neuropathic pain includes:…”
Section: Introductionmentioning
confidence: 99%
“…non-steroidal anti-inflammatory drugs (ketorolac), opioids (morphine), tricyclic antidepressants (amitriptyline, duloxetine), and some anticonvulsants (gabapentin); 6 however, all these drugs have shown moderate efficacy, often being associated with adverse effects and use of opioid drugs, in most of the patients have generated addiction and its excessive use even produced death by overdose. 5 Classic analgesic drugs such as morphine, codeine and aspirin have been isolated from natural products, which has attracted the attention of many researchers as a source that could provide the discovery of new analgesic drugs. 5,7 In addition, medicinal plants and their metabolites have a reduced number of side effects and they are used as an unexpensive therapeutic resources for management of chronic pain.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation